Is Oral Health Problems One of the Reasons for Encounters in Medical Primary Care Clinics in Malaysia A Pilot Epidemiological Study Among Selected Three Medical Primary Care Clinics in Kuantan, Malaysia - Tin, Myo Han; Md Aris, Mohd Aznan; Thuraiappah, D. M; Tin, Maung Aung; Tun Ismail, Tuan Sahardi; Sulong, Robiatu Adawiyah (2014)
Introduction: Primary care physicians provide a wide range of care including oral health problems (OHPs). However, epidemiological studies on OHPs in medical primary care clinics (MPCCs) are still limited. The prevalence of patients with OHPs in MPCCs and their epidemiological variables were verified in this study. Methods: A comparative cross-sectional study was conducted among three different MPCCs – university clinic (IIUM), public clinic (Balok) and private clinic (Clinic Ar Razi) in Kuantan from April 2012 to March 2013. Data of patients with OHPs were extracted from patient’ registers and their age, gender, reason for encounter (RFE)and consultation time (day or night) were noted. Interval prevalence was considered for the study. An exploratory analysis between patients’ epidemiological variables and RFE among three different clinics was done. Results: Out of a total of 84,251 patients, 605 patients with OHPs were identified. The prevalence of OHPs in the university, public and private clinic was 9.3, 10.9 and 5.4 per 1000 patients per year, respectively. In the private clinic, 58% of cases were night-calls. The mean (±SD) age of patients from the university, public and private clinic was 22.8(±11.7), 23.1(±17.6) and 17.9(±18.8) years, respectively. The male and female ratio in university, public and private clinic was (36.5% vs. 63.5%), (44.4% vs. 55.6%) and (50.8% vs. 49.2%), respectively. The RFEs were mouth ulcer (50.4%), gingivitis (17.7%), toothache (12.6%), mouth pain (8.9%), hand-foot-mouth-disease (7.8%), gum abscess (1.8%), more than one OHP (0.5%) and teething (0.3%). Although there were no significant differences between age groups and RFEs of patients with OHPs who attended the university clinic, it was significant in the other two clinics (p<0.05). Conclusion: This study highlighted that OHPs was one of RFEs in MPCCs. The epidemiological findings of the study will be valuable for health planners to provide better OH care in MPCCs.